2016
DOI: 10.18632/oncotarget.11757
|View full text |Cite
|
Sign up to set email alerts
|

Targeted suppression of AR-V7 using PIP5K1α inhibitor overcomes enzalutamide resistance in prostate cancer cells

Abstract: One mechanism of resistance of prostate cancer (PCa) to enzalutamide (MDV3100) treatment is the increased expression of AR variants lacking the ligand binding-domain, the best characterized of which is AR-V7. We have previously reported that Phosphatidylinositol-4-phosphate 5-kinase alpha (PIP5Kα), is a lipid kinase that links to CDK1 and AR pathways. The discovery of PIP5Kα inhibitor highlight the potential of PIP5K1α as a drug target in PCa. In this study, we show that AR-V7 expression positively correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Recent high-throughput RNAi screening identified checkpoint kinase 2 ( CHK2 ) as a tumour suppressor in PCa; CHK2 negatively regulates CDK1, forming a signalling loop with AR ( Ta et al , 2015 ). Furthermore, AR-V7 interacts with CDK1 and phosphatidylinositol-4-phosphate 5-kinase alpha to induce metastatic growth and treatment resistance ( Sarwar et al , 2016 ). Therefore, CDK1 inhibitors may be promising novel CRPC therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent high-throughput RNAi screening identified checkpoint kinase 2 ( CHK2 ) as a tumour suppressor in PCa; CHK2 negatively regulates CDK1, forming a signalling loop with AR ( Ta et al , 2015 ). Furthermore, AR-V7 interacts with CDK1 and phosphatidylinositol-4-phosphate 5-kinase alpha to induce metastatic growth and treatment resistance ( Sarwar et al , 2016 ). Therefore, CDK1 inhibitors may be promising novel CRPC therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…The AR is normally activated by DHT, a testosterone derivative synthesized by 5aR. It was shown by Sarwar et al [11] that PIP5K1a additionally binds to AR and the constitutively active AR variant V7 promoting protein stability leading to cancer progression. Inhibition of AKT by pleckstrin homology domain and leucine-rich repeat protein phosphatase and its chaperone FK506 binding protein 5 and inhibition of the receptor tyrosine-protein kinase erbB-2/3 (HER2/HER3) by mTOR lead to a reciprocal feedback mechanism between PI3K/AKT/mTOR and AR signaling as described by Carver et al in mice with PTEN-deficient tumors [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recently reported study revealed that binding of ISA-2011B to PIP5K1a interrupts the AR/PIP5K1a protein complex and thus makes it more accessible for proteasome-dependent degradation. This could be an indication that ISA-2011B acts as a destabilizing agent to reduce PIP5K1a expression level in PCa cells, and not via reducing the activity on the enzymatic level [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations